Design and Analysis of a Hybrid Exoskeleton for Upper Limb Rehabilitation - Wang Zheng; Liu Fanghua; Shao Jiawei; Wu Wanyi; Di Cheng (Jixie chuandong)
Aiming at the balance between the accuracy, stability and exoskeleton volume of the existing upper limb exoskeleton, an 8-degree-of-freedom （DOF） hybrid upper limb rehabilitation exoskeleton robot is proposed. A new 2-degree-of-freedom elbow rehabilitation device is designed to replace the traditional single-degree-of-freedom elbow exoskeleton in order to better achieve elbow training for patients with upper limb movement disorders. A 3RRR/S mechanism with coaxial spherical surface is designed for hand rehabilitation, which can make the rehabilitation training of hand more enveloping. The coordinate system is established according to the hybrid exoskeleton mechanism, the kinematic model of the rigid body part of the mechanism is established by using the vector loop method, and the working space nephogram of the mechanism is drawn by Monte Carlo method to verify that it meets the space requirements for rehabilitation training. Finally, the trajectory planning of a typical motion is carried out by Matlab, and the smooth trajectory of the terminal centroid motion is obtained by Adams to verify the rationality of its kinematic analysis and structural design. The maximum load attitude is simulated by constrains the excess degrees of freedom, and the load characteristic curve is drawn, which lays the foundation for the selection of the drive and the construction of the prototype.